Cropping practices of globe artichoke: a bibliometric study - Stea, Donato; Sellami, Mohamed Houssemeddine; Ruta, Claudia; Pulvento, Cataldo; De Mastro, Giuseppe (Frontiers in Sustainable Food Systems, 2023)
Globe artichoke is a food plant that is gaining increasing interest due to its commercial, nutritional and therapeutic value; research and development in the field of agriculture for this crop encompasses several key areas to enhance cultivation, productivity, and overall sustainability. In this study a bibliometric analysis of literature has been carried out in order to identify research areas and research gaps in cropping management of globe artichoke under field conditions, and to identify new research opportunities. The analysis revealed that published articles on the agronomic practices of globe artichoke under field conditions, is concentrated in Europe (70.56%), followed by North America (10%) and South America (7.22%). On the vastly arid Australian continent, there is a dearth of such studies. Italy, Spain and USA, were the most productive countries in the globe artichoke research field. The analysed papers have also shown that agronomic practices such as irrigation (wastewater and brackish water), fertilization, diseases management and plant breeding are the most studied cropping practices that affect artichoke yield and head quality. Finally, this study highlights the importance of integrating innovative methods like meta-analysis to gain a more holistic comprehension of how agricultural practices impact globe artichoke and to lays the groundwork for future research endeavours.